The Benefits of Executive Control Training and the Implications for Language Processing - Hussey, Erika K.; Novick, Jared M. (Frontiers in Psychology, 2012)
Recent psycholinguistics research suggests that the executive function (EF) skill known as conflict resolution—the ability to adjust behavior in the service of resolving among incompatible representations—is important for several language processing tasks such as lexical and syntactic ambiguity resolution, verbal fluency, and common-ground assessment. Here, we discuss work showing that various EF skills can be enhanced through consistent practice with working memory tasks that tap these EFs, and, moreover, that improvements on the training tasks transfer across domains to novel tasks that may rely on shared underlying EFs. These findings have implications for language processing and could launch new research exploring if EF training, within a “process-specific” framework, could be used as a remediation tool for improving general language use. Indeed, work in our lab demonstrates that EF training that increases conflict-resolution processes has selective benefits on an untrained sentence-processing task requiring syntactic ambiguity resolution, which relies on shared conflict-resolution functions. Given claims that conflict-resolution abilities contribute to a range of linguistic skills, EF training targeting this process could theoretically yield wider performance gains beyond garden-path recovery. We offer some hypotheses on the potential benefits of EF training as a component of interventions to mitigate general difficulties in language processing. However, there are caveats to consider as well, which we also address.